Confucius Institute at Universitas Al Azhar, Jakarta; The unseen power of China - Lan, Thung Ju (Wacana, Journal of the Humanities of Indonesia, 2017)
China's soft power is a difficult concept to measure if the Confucius Institute is the only source relied on. Joseph Nye's concept of soft power puts a strong emphasis on "the power of attraction" as a tool to persuade or "to shape the preferences of others" in the worlds of business and politics. To understand how this soft power - or the Confucius Institute - works, we have to determine the "observable" power of the "intangible" attraction embedded in it. This observable but intangible attraction is assumed to be "embedded"in the language and culture offered by the Institute, namely so-called "shared values". However, without having attended its classes, it is difficult to see which values are being shared with the local students. Despite this handicap, it is very apparent that the image of China itself has acted as an attraction. An attraction to China was visible already, even before the Confucius Institute was established. For Indonesians, China is a big country which has exerted its power there for a long time through its diaspora and/or exports. Therefore, the Confucius Institute is just one of the many forms of Chinese-ness within their purview. Certainly, the Confucius Institute might have assisted in adjusting negative impressions and expelling some of the reservations the Indonesians have about China. Nevertheless, its influence extends to only a limited number of people who are closely engaged with the Institute.